The Message of Da’wah in Donggia Tourist Destination in Kahayya Village, Kindang District, Bulukumba Regency (Da’wah Review) - Wahyuni; Amin, Muliaty; Tajibu, Kamaluddin (Jurnal Mercusuar, 2022)
The main problem of this research is how to convey the message of da’wah (Islamic preaching) to the natural tourist destination of Donggia in Kahayya Village, Kindang District, Bulukumba Regency. This research used a qualitative descriptive method with the approach of da’wah studies, phenomenological approach, and sociological approach. The sources of research data were obtained directly from the Head of Kahayya Village, the Head of Kahayya Hamlet, the manager of the Donggia natural tourist destination, and tourists who visited the natural tourist destination of Donggia. Furthermore, the data collection methods used were observation, interviews, documentation, and searching from various literature or references. The data processing and analysis techniques were carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results of this research show that: The message of da’wah at the natural tourist destination of Donggia in Kahayya Village, Kindang District, Bulukumba Regency are: a) Moral message by increasing faith through Tadabbur Alam (contemplation of nature), for example, reciting prayers and remembrance (zikir), instilling values of faith in kindergarten/TPA children through learning in nature, and fostering love for nature, for example, not damaging the surrounding plants, planting 1000 trees, and practicing cleanliness as part of worship; b) Strengthening Ukhuwah Islamiyah (Islamic brotherhood) or friendship, for example, resting with family and colleagues, inclusive camping every year, and celebrating Kahayya coffee; c) Adding knowledge and inspiration. Economic factors include supporting community welfare; livelihood as a supporting factor, and Istana Kahayya coffee UMKM (Micro, Small, and Medium Enterprises). Health factors include: a) Becoming one with nature can maintain mental health, such as reducing stress levels, increasing happiness, and increasing the immune system.